Designing a Course with Critical Thinking Focus : Developing Basic English Skills for the Students of Computer Science and Engineering at a Private University of Bangladesh (Global Journal of Human-Social Science, 2018)
This article suggests some critical thoughts about a four months English course for the students of Computer Sciences and Engineering titled 'Developing Basic English Skills" for general academic and professional purposes. The primary aim of this paper is to exhibit how the course can be designed by critical thinking and by following some well-established strategies with the help of needs analysis. Some new approaches like flipped approach along with lecture and multimedia presentation the class was conducted by the researcher for the group of students from CSE, first semester in a private university in Bangladesh.
Keywords: strategies; designed by critical thinking; developing basic english skills; flipped approach; course design